Rancang Bangun Kontrol Charger Station Dengan Panel Surya Berbasis Mikrokontroler - Latifah, Wahyu; Nuzuluddin, M.; Komala Dewi Patwari, Intan (Fakultas Teknik Universitas Hamzanwadi, 2024)
Charger station is one of the facilities needed by smartphone users, especially in public places such as tourist sites. Because there are still many battery charging places that use PLN electricity, so it is less effective when it is far from the reach of PLN electricity. Based on these problems, this research tries to provide a solution, namely developing a charger station at tourist sites through the use of solar panels and coin acceptors as a payment system for the charger facility, so that visitors can charge their smartphones easily and at a very affordable cost. The research method used is the R&D research method, while the development model is the ADDIE model. In building this charger station, several main components are needed, such as 20WP solar panels, 12V.12A batteries, 10A PWM Solar Charge Controller (SCC), 220W inverter, coin acceptor, arduino, push button, 16x2 LCD, and relay. The test results show that the battery charging process depends on the condition of sunlight intensity. When charging the battery from the solar panel, several times the voltage on the SCC fluctuates when it reaches 14.3V. However, when it has not reached 14.3V or when the inverter is active, the voltage on the SCC stabilizes. Then when the solar panel is no longer charging the battery or is removed from the SCC, then allowed to stand for a while, the voltage on the SCC will decrease by itself, after several checks, the voltage will drop by about 0.2V or 0.3V. While the results of testing coins that have been calibrated by the coin acceptor show a success rate of 80% for the Rp500 coin (silver) and for the Rp1000 coin shows 96.7% success after 30 tests. Overall, this system can run according to the design made, although there are still some shortcomings such as limited battery capacity, the size of the solar panel power that is still minimal and the selection of the type of SCC that has not been maximized.Keywords: Charger station, Microcontroller, Solar panels